Desired weight loss and its association with health, health behaviors and perceptions in an adult population with weight excess: One-year follow-up - Bouzas, Cristina; Bibiloni, Maria del Mar; Garcia, Silvia; Mateos, David; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Goday, Albert; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; et al. (Frontiers in Nutrition, 2022)
Background: Metabolic syndrome (MetS) deteriorates quality of life and increases mortality. Weight dissatisfaction in patients with MetS might modify the effect of lifestyle interventions on successful changes in health-related behaviors. Objective: To assess 1-year changes in cardiovascular risk scores, self-perceived general health, and health-related behaviors according to observed changes in desired weight loss over the first year of intervention in a large cardiovascular prevention trial. Design: Prospective analysis of the PREDIMED-PLUS trial including 5499 adults (55-75 years old) with overweight or obesity at baseline. Methods: Desired weight loss was the difference between ideal and measured weight. Roughly tertiles of change in desired weight loss (1-year vs. baseline) were defined by the following cut-off points: ≥0.0 Kg (T1, n=1638); 0.0 to -4.0 Kg (T2, n=1903); ≤-4.0Kg (T3, n=1958). A food frequency questionnaire assessed diet and the Minnesota-REGICOR questionnaire assessed physical activity. The Framingham equation assessed cardiovascular risks. Changes in the severity of the MetS were also evaluated. The Beck Depression Inventory assessed depressive symptoms and the SF-36 appraised health-related quality of life. Data were analyzed using General Linear Models. Results: BMI decreased in T2 and T3 (T1: 0.3; T2: -0.7. T3: -1.9). The highest improvement in diet quality were observed in T3. Cardiovascular risk decreased in T2 and T3. Mean reductions on MetS severity score were: -0.02 for T1, -0.39 for T2, and -0.78 for T3. Physical health perception’s increases across successive tertiles. Conclusions: In aged adults with MetS, more ambitious goals for desired weight loss were associated with improvements on diet, cardiovascular health, and physical health perception, during the first year of a healthy-lifestyle intervention program. Weight dissatisfaction should be considered by health care professionals.